Multiple case study applied in nursing research: a case report - Lara Adrianne Garcia Paiano da Silva; Nen Nalú Alves das Mercês
ABSTRACT Objective: To report the experience of using the method of multiple case study. Method: We used the method of multiple case study, conducted with children and adolescents assisted in the pediatric oncology inpatient unit. Results: The steps used for the development of a multiple case study were: Step 1 - Define and design; Step 2 - Prepare, collect and analyze; Step 3 - Analyze and complete. The steps included the development of a research project with the definition of its components, preparation of protocol for the case study, data collection, individual report of cases, data analysis and final report with data cross-referencing. Conclusion: The case study method can be used by nurses and contribute to the advancement in knowledge of nursing as a science and therefore contribute to a full care practice in the context in which the phenomenon happens.